Intelligent Avatars, Holographic Tools, Digitized Objects: An Extended Reality Simulation Demonstration - Salvetti, Fernando; Gardner, Roxane; Minehart, Rebecca; Bertagni, Barbara (International Journal of Advanced Corporate Learning (iJAC), 2023)
How can we design engaging and effective medical education both online and on site? Extended reality (XR) is a term referring to all real-and-virtual combined environments and human-machine interactions generated by computer technology and wearables. It includes representative forms such as AR, VR, and MR, and the areas interpolated among them. MR is a domain of particular interest today: It takes place not only in the physical world or in the virtual world, but is a mix of the real and the virtual. Metaverses can be enabled by MR wearable augments. Glasses-free MR is another very interesting dimension: e-REALâ, as a MR environment for hybrid simulation and medical education in general, can be a stand-alone solution or even networked between multiple places through a link to a special videoconferencing system. Digital humans and human-sized holograms are part of the e-REAL scenarios, making this solution unique, rich, and diversified.